Sex-biased genetic effects on gene regulation in humans. - Dimas, A; Nica, A; Montgomery, S; Stranger, B; Raj, T; Buil, A; Giger, T; Lappalainen, T; Gutierrez-Arcelus, M; McCarthy, M; Dermitzakis, E (2012)
Human regulatory variation, reported as expression quantitative trait loci (eQTLs), contributes to differences between populations and tissues. The contribution of eQTLs to differences between sexes, however, has not been investigated to date. Here we explore regulatory variation in females and males and demonstrate that 12%-15% of autosomal eQTLs function in a sex-biased manner. We show that genes possessing sex-biased eQTLs are expressed at similar levels across the sexes and highlight cases of genes controlling sexually dimorphic and shared traits that are under the control of distinct regulatory elements in females and males. This study illustrates that sex provides important context that can modify the effects of functional genetic variants.